PEMANFAATAN PROGAM ADAPTASI TEKNOLOGI PADA GOOGLE SPREADSHEETS SEBAGAI MEDIA PENILAIAN UNTUK GURU - Fulusia Nurmawati; Ricardo, Angga; Ardika, Alif (Abdi Masya, 2024)
Global world changes have also brought about various increasingly sophisticated technological tools, including in the world of education. It is necessary to improve teacher quality as a balance to the progress of education 4.0, one of which is increasing teacher digital competence. However, the reality on the ground is that there is still a state of technological lag. This research focuses on (1) knowing the intensity of use of digital devices in learning, (2) knowing the computer application programs most often used in learning, and (3) knowing teachers' mastery in using computer application programs for learning. This research used a descriptive survey involving 70 elementary school teachers using random techniques. The data collection instrument is in the form of a questionnaire accompanied by data collection through interviews and observation activities. Results of dedication. This activity was carried out at Gersi Elementary School which is located in Blora District, Blora Regency. The method in this service program is lectures conducted offline in two directions.  The results of this service program are that this teaching materials training assistance is very effective in providing teachers in Blora with knowledge about developing mathematics teaching materials and providing examples and knowledge about teacher creativity